PERCEPTIONS OF LECTURERS AND STUDENTS REGARDING THE USE OF ENGLISH IN THE EMI CLASSROOM - Le Thi Tuyet Hanh*, Thai Phan Tu Van, Nguyen Thi Nguyet Ha (Tạp chí Khoa học)
This study investigates and compares the perceptions of EMI lecturers and their students regarding lecturers' use of English in English-medium instruction (EMI) classrooms. Data were collected through surveys and interviews with 252 lecturers from various Vietnamese universities and 162 students enrolled in EMI programs. The results show that lecturers generally express confidence in their English proficiency for teaching and classroom management. Similarly, students rated their lecturers' English competence highly. However, discrepancies between the two groups' evaluations highlight the need for greater alignment in perceptions to improve the overall effectiveness of EMI instruction.